2021
DOI: 10.1038/s41598-021-83837-2
|View full text |Cite|
|
Sign up to set email alerts
|

Postural adjustments impairments in elderly people with chronic low back pain

Abstract: Chronic low back pain (CLBP) is associated with postural control impairments and is highly prevalent in elderly people. The objective of this study is to verify whether anticipatory postural adjustments (APAs) and compensatory postural adjustments (CPAs) are affected by CLBP in elderly people by assessing their postural control during a self-initiated perturbation paradigm induced by rapid upper arm movement when pointing to a target. The participants’ lower limb muscle onset and center of pressure (COP) displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Static balance is controlled in a complex way by different sensory (visual, vestibular, proprioceptive, and tactile) and neuromotor systems (involving both sensory integration and movement planning to cortical control of standing and spinal reflex action resulting in changes in joint stiffness and damping; Goodman & Tremblay, 2021;Kang et al, 2013;Winter et al, 1998). Older people show altered motor strategies compared to young and healthy people, either for balance maintenance tasks or postural anticipation in the face of destabilization (Garcez et al, 2021;Woollacott & Manchester, 1993). But, in addition to the difficulty of studying the interactions between these systems and their actions in posture maintenance, there is a lack of interpretability of the COP variables (Palmieri et al, 2002), which is enhanced by the diversity of methods for calculating them.…”
Section: Discussionmentioning
confidence: 99%
“…Static balance is controlled in a complex way by different sensory (visual, vestibular, proprioceptive, and tactile) and neuromotor systems (involving both sensory integration and movement planning to cortical control of standing and spinal reflex action resulting in changes in joint stiffness and damping; Goodman & Tremblay, 2021;Kang et al, 2013;Winter et al, 1998). Older people show altered motor strategies compared to young and healthy people, either for balance maintenance tasks or postural anticipation in the face of destabilization (Garcez et al, 2021;Woollacott & Manchester, 1993). But, in addition to the difficulty of studying the interactions between these systems and their actions in posture maintenance, there is a lack of interpretability of the COP variables (Palmieri et al, 2002), which is enhanced by the diversity of methods for calculating them.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent studies reported impaired or altered APAs in musculoskeletal diseases. Garcez et al [12] reported that elderly patients who had chronic low back pain demonstrated impaired postural control and less efficient APAs. Takeuchi et al [13] reported impaired APAs in patients with hip osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, inadequate initial physical reaction due to impaired APAs may lead to falls. To date, impaired and altered APAs were reported in the elderly population and in those with Parkinson's disease, stroke, and chronic low back pain [7][8][9][10][11][12][13][14]. To the best of our knowledge, there are no reports that investigated APAs in cervical myelopathy patients.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, investigating the postural sway and physical activity levels of osteoporosis faller and nonfaller groups is necessary to indicate who is more prone to fall and mitigate the risk of bone fracture. Moreover, age/gender-matched comparison of faller and non-faller in osteoporosis patients is essential because it minimizes age-related confounds, such as muscle, bone density, vestibular, and vision deterioration, where these aspects significantly differ among the various ages and dictates the capability of postural stability ( 14 ). The objective of this study is to analyze the disparities between fallers and non-fallers age/gender-matched osteoporosis patient's postural stability, and physical activity levels, and to elucidate how the fall status leads to a decrease in both the postural stability and physical activity levels.…”
Section: Introductionmentioning
confidence: 99%